Research on the cultivation of sustainable development ability of higher vocational students by creative thinking teaching method - Li, Xin-Zhu; Chen, Chun-Ching; Kang, Xin (Frontiers in Psychology, 2022)
Education for sustainable development (ESD) is an important guideline for United Nations Sustainable Development Goals. Students’ creative thinking can be applied to various disciplines, promoting sustainable learning. Most of Taiwan's beauty and hairdressing technical education teachers mainly teach students to imitate, and students' works lack creativity and thinking. A total of 43 higher vocational college students participated, 23 of whom were in the experimental group using the creative thinking teaching method and 20 of whom were in the control group using the traditional teaching method. The results show that the creative thinking teaching method can effectively improve students' learning outcomes in the multimedia material creation course, including breaking through the limitation of thinking, putting forward different ideas and answers, and constantly innovating, to make the presented results more creative and meaningful. The creative thinking teaching methods solve students’ trouble in creative problem solving, enhance students’ problem solving and critical thinking skills, and improve students’ involvement in the study.